**If p+q+r = 1 and pq+qr+pr = -1, and pqr = -1, find the value of **

Pq+qr+pr= pqr (because they are both equal to -1)

then you divide both sides by p to get

q+ qr/p + r = qr. then you divide both sides by q and get

r/p + r/q = r. so I divided both sides by r to get

P + q =0 therefore p= -q. putting that into the first equation allows you to get that r=1 because p and q cancel each other out. then I put that into pq+qr+pr=-1 so pq+q+p=-1 since p=-q the q+p gets canceled out and you're left with pq=-1 and since it is the product of the two numbers and q is the negative of p. q=-1 while p=1. therefore p=1 r=1 and q=-1

If your question is not fully disclosed, then try using the search on the site and find other answers on the subject Mathematics.

Find another answersMathematics, published 11.05.2023

Mathematics, published 23.03.2023

Use the equation to identify the center and radius of the circle (X+3)^2+(y-7^2=11

Mathematics, published 27.05.2023